Standards of proof in the criminal procedure of the United States of America and Ukraine: A comparative research - Басай, Віктор Давидович; Басай, В. Д.; Басай, Виктор Давыдович; Basai, Viktor D.; Гринюк, Володимир Олексійович; Гринюк, В. О.; Гринюк, Владимир Алексеевич; Hryniuk, Volodymyr O.; Ковальчук, Сергій Олександрович; Ковальчук, С. О.; Ковальчук, Сергей Александрович; Kovalchuk, Serhii O. (Editorial Primmate S. A. S., 2019)
The purpose of the paper is disclosure of the concept, features of the formation of the system and mechanism of application of the standards of proof in the criminal procedure of the common law and continental legal systems (on the example of the USA and Ukraine). In result of the research, the concept, features of the system and the mechanism of application of the standards of proof in the criminal procedure of the USA and Ukraine were compared, which revealed the similarities and differences between them. According to the results of the research of the concept of the standards of proof in the criminal procedure of the USA and Ukraine, their signs were distinguished, which made it possible to conclude that their concept is approximated in the criminal procedure doctrine of the mentioned countries. In the criminal procedure both the USA and Ukraine, the standards of proof reflect the requisite level of knowledge about the facts and circumstances of criminal proceedings that a decision-maker must reach to make it. The differences in the formation of the system of the standards of proof in the criminal procedure of the USA and Ukraine were established. In the criminal procedure of the USA, they were formed in the judicial practice and subsequently reflected in the Model Code of Criminal Procedure. In the criminal procedure of Ukraine, they first gained regulatory support in the Criminal Procedure Code of Ukraine from 2012, after which they found application in the judicial practice, which, at the same time, consistently takes into account the experience regarding their content, given in the judgments of the European Court of Human Rights.

Мета статті полягає у розкритті концепції, особливостей формування системи та механізму застосування стандартів доказування у кримінальному процесі загальноправової та континентальної правової систем (на прикладі США та України). В результаті проведеного дослідження спіставлено поняття, особливості системи та механізм застосування стандартів доказування у кримінальному процесі США та України, що дозволило виявити схожість та відмінності між ними. Вивчення концепцій стандартів доказування у кримінальному процесі США та України сприяло виділенню їх ознак, на підставі яких зроблено висновок про наближеність цих концепцій у кримінально-процесуальній доктрині даних країн. У кримінальному процесі як США, так і України стандарти доказування відображають необхідний рівень знань про факти та обставини кримінального провадження, яких повинна досягти уповноважена на прийняття рішень особа. Встановлено відмінності у формуванні системи стандартів доказування у кримінальному процесі США та України: у кримінальному процесі США вони були сформовані в судовій практиці і згодом відображені в Модельному кримінально-процесуальному кодексі; в кримінальному процесі України вони вперше набули нормативно-правового закріплення в Кримінально-процесуальному кодексі України з 2012 року та застосування в судовій практиці, яка, водночас, поступово враховує й досвід щодо їх змісту, відображений у рішеннях Європейського суду з прав людини.
Basay V. Standards of proof in the criminal procedure of the United States of America and Ukraine: A comparative research / V. Basay, V. Hryniuk, S. Kovalchuk // Amazonia Investiga. – Vol. 8. – Iss. 22. – Editorial Primmate S. A. S., 2019. – P. 550-559.
Keywords: proof; standards of proof; inner conviction; assessment of the evidences; criminal proceeding; доказ; стандарти доказування; внутрішнє переконання; оцінка доказів; кримінальне провадження; Research Subject Categories::LAW/JURISPRUDENCE